The effects of climate factors, population density, and vector density on the incidence of dengue hemorrhagic fever in South Jakarta Administrative City 2016-2020: an ecological study - Amelinda, Yuri Shizcha; Wulandari, Ririn Arminsih; Asyary, Al (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus (DENV) and is transmitted through the bite of the Aedes aegypti and Aedes albopictus mosquitoes. This study aims to analyze the relationship between the incidence of DHF which can be influenced by climatic factors in the same month (non-time lag), climatic factors with a lag of 1 month (time lag 1), climatic factors with a lag of 2 months (time lag 2), population density, and vector density.Methods: The study design used is an ecological study. The data is sourced from the South Jakarta City Administration of Health, the South Jakarta City Administration of Central Statistics, and the Meteorology, Climatology and Geophysics Agency. Data were analyzed using correlation test.Results: The results showed that the incidence of DHF was related to non-time lag rainfall, time lag 1, and time lag 2, air temperature time lag 2, air humidity non-time lag, time lag 1, and time lag 2, population density, and numbers of mosquito’s larvae free index (ABJ).Conclusions: DHF is still a disease that needs to be watched out for in the South Jakarta Administrative City, requiring the government and the people of the South Jakarta Administration to continue to increase efforts to prevent and control DHF.